Electrochemical corrosion behavior of tantalum coated 316L stainless steel by D.C. Magnetron sputtering for orthopedic applications - Pathote D.; Jaiswal D.; Singh V.; Behera C.K. (My University, 2025)
The austenitic stainless steel type 316L was engineered with a thin multilayer of tantalum with a thickness of 1.504µm, 3.893 µm and 6.083µm and a duration of 15, 30 and 60 minutes, respectively, by the DC Magnetron Sputtering. Electrochemical behaviors of all three samples were investigated by potentiodynamic and electrochemical impedance spectroscopy techniques. Simulated body fluid was used as the corrosive medium for the electrochemical measurement. The highest corrosion resistance was obtained for the sample subjected to 60 minutes of Ta deposited on 316L S.S. according to EIS measurements, and the lowest corrosion rate of 0.0047 mm/year was obtained for the same sample according to the PD measurements. All the measurements were carried out after the determination of open circuit potential (OCP) at 37˚C with 1 ±°C. All the samples were then characterized by scanning electron microscopy (SEM) to observe the morphology of coating after corrosion. The number of corrosion pits observed from the SEM micrograph was much less on the three coated samples compared to the bare sample. X-ray Photoelectron Spectroscopy (XPS) was used to identify the chemical states of coated and bare 316L SS. Ta4f is present as oxidation states in Ta coated stainless steel 316L, whereas Ta4f is the main species examined along with other elements (C1s, N1s, O1s, Cr2p, Fe2p, Ni2p, and Mo3d). It was also observed that there was strong adhesion between substrate and Ta-coating. After the potentiodynamic studies, results show a significant improvement in corrosion resistance attributed to the strong, stable oxide layer formation. © 2022 The Authors